2001
DOI: 10.1074/jbc.m006454200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2A Activates the HIV-2 Promoter through Enhancer Elements That Include the pets Site

Abstract: Human immunodeficiency virus type 2 (HIV-2) gene expression is regulated by upstream promoter elements, including the peri-Ets (pets) site, which mediate enhancer stimulation following treatment with the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA). We previously showed that the oncoprotein DEK binds to the pets site in a site-specific manner. In this report, we show that binding to the HIV-2 pets site is modulated by treatment of U937 monocytic cells with TPA, an activator of protein kinase C. TPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 39 publications
7
43
1
Order By: Relevance
“…These data indicate that the more acetylated form of DEK has a 3-to 4-fold decrease in affinity for DNA, as compared with less acetylated forms of DEK. These data are consistent with the general observation that TSA activates transcription, and the finding that DEK likely plays a role in transcriptional repression (15,16).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These data indicate that the more acetylated form of DEK has a 3-to 4-fold decrease in affinity for DNA, as compared with less acetylated forms of DEK. These data are consistent with the general observation that TSA activates transcription, and the finding that DEK likely plays a role in transcriptional repression (15,16).…”
Section: Resultssupporting
confidence: 91%
“…Acetylation of DEK Decreases Affinity for DNA-We have previously demonstrated that DEK binds to the TG-rich pets site from the HIV-2 promoter and that dephosphorylation of endogenous DEK results in release of DEK bound to this site (14,15). These data indicate that, similar to many other proteins, post-translational modifications may play a significant role in the function of DEK within cells.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations